Superior Improvements in Knee Pain and Function with a Novel Synthetic Medial Meniscus Replacement Implant Compared to Non-surgical Care in Subjects with Knee Pain Following Partial Meniscectomy: Two-year Results from Two Prospective US Clinical Trials. Issue 7 (30th July 2021) - Hershman, Elliott; McKeon, Brian; Kaeding, Christopher; Edelson, Richard; Greenleaf, Jonathan; Gersoff, Wayne
Objectives: Arthroscopic partial meniscectomy (APM) is the most common surgical treatment for symptomatic, irreparable meniscal tears that do not improve with non-surgical care. For many patients, APM is associated with improvements in knee pain and function, but a subset of patients reports persistent or recurrent knee pain 1-2 years after APM surgery. Current treatment options for post-APM knee pain are limited, especially for patients considered too young for knee replacement. The polymeric medial meniscus implant mimics the biomechanical function of the natural medial meniscus and is intended to provide relief from pain and improved function in subjects with knee pain following APM. Two FDA-regulated clinical trials were conducted in the United States and pooled for analysis, to assess superiority of a synthetic medial meniscus implant to non-surgical care in treating persistent or recurrent knee pain following previous partial meniscectomy. The hypothesis was that the meniscus implant is superior to non-surgical care for improvements in composite measures of knee-related pain, function, and quality of life at 2 years of follow-up. Methods: 242 patients (176 investigational, 66 control) were treated in 2 prospective, concurrent clinical trials in the U.S.: a randomized controlled superiority trial (RCT) comparing the medial meniscus implant to non-surgical care (control) and a single-arm, implant-only trial. Eligible subjects had persistent knee pain and one or more previous partial meniscectomies at least 6 months before trial entry. Treated subjects returned for follow-up visits at 1.5 months, 6 months, 1 year, and 2 years. Patient-reported knee pain, function, and quality of life were assessed using the Knee Injury and Osteoarthritis Outcome Score (KOOS). The primary patient-reported outcomes were 2 KOOS subscales: KOOS Pain and KOOS Overall. KOOS success was defined as subjects who achieved either (1) KOOS Pain ≥86.1 at 2 years and KOOS Overall ≥86.2 at 2 years or (2) a ≥20-point improvement from baseline to 2 years in KOOS Pain and KOOS Overall, with KOOS Pain ≥40 at 2 years. Treatment cessation was defined as any subject who discontinued the per-protocol treatment by permanent implant removal (implant group) or any surgical procedure on the index knee (control group). Implant subjects who underwent subsequent surgical procedures on index knees (e.g. implant exchange) remained in the trial. The two treatment groups were well-matched, except for baseline KOOS Sports and Recreation. Statistical analyses adjusted for high vs low baseline KOOS Sports and Recreation using 2-factor analysis of variance (ANOVA) for continuous variables and 2x2 logistic regression for dichotomous variables. Results: Sixteen subjects (6.6%; 14 control, 2 implant) were lost to follow-up or withdrew from the study over 2 years. The magnitude of improvement from baseline to 2 years was significantly greater in the implant group compared to control for 5 of 6 KOOS subscales (Figure 1), including the primary outcomes of KOOS Overall and KOOS Pain (Figure 1A, B). The proportion of subjects who achieved KOOS success was significantly higher in the implant group (63.4%) than the control group (27.9%), which remained true with or without the adjustment for baseline KOOS Sports and Recreation ( P <.0001 in each case). Treatment cessation through 2 years was less frequent in the implant group (10.5%) compared to the control group (17.3%), but the difference was not statistically significant ( P =.19). Conclusions: Two-year results from 2 prospective, concurrent, US clinical trials demonstrate that the synthetic meniscus implant provides superior relief from post-APM knee pain when compared to treatment with non-surgical care alone. In addition, the magnitude of change from baseline to 2 years in the primary patient-reported outcomes and the rate of KOOS success significantly favored the implant group compared to the control group. Subjects in the implant group tended to discontinue treatment at a lower rate compared to subjects in the control group, but the difference was not statistically significant. Subjects treated with the implant who underwent a device exchange or repositioning procedure were able to continue treatment therapy with the medial meniscus implant. Overall, the implant group experienced superior improvements and outcomes at 2 years compared to subjects receiving non-surgical care alone. :